An investigation on demands of clinical teaching among nursing undergraduates at school (在校本科护生临床教学需求调查分析) - GAN Lu (甘露); XIE Wei (谢薇); SHUAI Xuemei (帅雪梅); XUE Ting (徐婷); NI Dangcheng (倪当承); RAO Liu (饶柳); YUAN Zheng (袁铮); JIN Liping (金莉萍); TANG Jia (唐佳); LI Wei (李伟) (中西医结合护理)
Objective To investigate the demands of clinical teaching and perception of the theoretical knowledge and clinical practice among nursing undergraduates at school, and provide reference for establishment of a systematic teaching management system and improve the quality of clinical teaching. Methods Totally 161nursing undergraduates at school were recruited by a convenience sampling method, and an open-ended questionnaire survey was conducted to investigate the nursing undergraduates’ demands of clinical teaching. Results The top-ranked demand for clinical teaching was the combination of theoretic knowledge and clinical practice (91. 93%), followed by the diversified teaching methods including video-assisted and real case teaching (85. 71%) and developing students' interest in clinical work(81. 99%). Most of students were satisfied with clinical teaching. Conclusion Clinical teachers should help students build clinical thinking ability by adopting the teaching method combining theory with practice. Clinical teachers should help students build conference and establish identity and self-worth in clinical practice. (目的 调查在校本科护理学生对临床带教老师的需求, 通过了解学生的理论知识与临床实践认知, 为建立系统、完善的教学管理体系, 不断探索完善临床护理实践与理论知识的紧密结合, 从而为提高临床护理教学质量提供参考。方法 采用便利抽样法对某高校161例在校本科护理学生进行临床教学需求问卷调查。结果 在校生护生对“应将书本理论与临床实操练习相结合”的需求最高(91. 93%), 其次为“教学多样化, 如视频、真实案例等教学”(85. 71%)和“教学过程中应培养学生对临床工作的兴趣”(81. 99%)。满意度调查显示, 156(96. 89%)例在校护生对教学满意。结论 在进行临床教学时, 教师可以通过现场理论与实操教学相结合的方式, 让学生建立自己的临床思维, 老师多分享临床经验, 多鼓励学生, 在潜移默化中帮助学生建立自信心, 帮助护理实习生在临床工作中找到自我价值, 从而提高护理教学质量。)